Results Readiness in Social Protection and Labor Operations - Rawlings, Laura; Honorati, Maddalena; Rubio, Gloria; Van Domelen, Julie (World Bank, Washington, DC, 2017)
The main focus of the social protection and labor portfolio is on strengthening client's institutional capacity in the design and implementation of programs, but projects are not well equipped to track progress in this area. Correspondingly, there is a need to strengthen approaches to measuring and monitoring a 'missing middle' of service delivery, precisely those areas for which counterpart institutions are responsible during the course of a project. In particular, better measures of the primary functions of social protection and labor agencies are needed, such as identifying and enrolling beneficiaries, targeting, payment systems, fraud and error control, performance monitoring of service delivery providers, responsiveness to citizens, transparency, efficiency, management information systems and monitoring and evaluation systems. New World Bank initiatives particularly standard core indicators by sector and the introduction of results based investment lending call for substantial improvements in the use of monitoring and evaluation (M&E). Impact evaluations are included in about half of projects and should continue to be used selectively and strategically, particularly when the program is innovative, replicable and/ or scalable to reach a broader set of beneficiaries, addresses a knowledge gap and is likely to have a substantial policy impact. Structuring evaluations around core themes with common outcome measures is fundamental to building a global knowledge base on development effectiveness.